Enhancement of Corrosion Resistance of MAO/Polydopamine/Polylactic Acid-Coated AZ31 Magnesium Alloy for Biomedical Applications - Annalisa Acquesta; Fulvia Desiderio; Pietro Russo; Giulia Stornelli; Andrea Di Schino; Tullio Monetta (Metals)
This paper aimed to investigate the enhancement of the corrosion resistance of a protective system applied on the AZ31 magnesium alloy to be used as an orthopedic biomedical device, composed of three different superimposed layers: (a) magnesium-based oxide, (b) polydopamine, and (c) polylactic acid. Specifically, morphological and chemical analyses, crystallographic, roughness, and micro-hardness were carried out. The electrochemical measurements were performed in Hanks’ Balanced Salt solution at 37 °C. The micro arc oxidation (MAO) treatment involved the classic pancake structure of the oxide with a consequent high extension of the real area.The sealing ofits pores via the polydopamine was well highlighted through the surface roughness analysis. As expected, the magnesium oxide layer reduced the degradation rate.The presence of polydopamine on the oxide layer improved the corrosion resistance of the alloy, showing a pseudo-passivity range in the potentiodynamic polarization curve, due to the filling of oxide pores.The highest impedance modulus in the electrochemical impedance spectroscopy analysis during the temporal observation of 168 h was observed when all coatings were applied on magnesium substrate, due to a synergetic action. Thus, the multilayers should represent a protective system to control the degradation process.